(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article dedicated to the analyses of theoretical and methodological bases of political science. World outlook and methodological bases of political science consists the complex of philosophic and general theoretical ideas about politics. Ideas of politics accumulates in the analyses, approaches and orientations of political cognition. In modern political science exists various methodological concepts of analyses of political life of society. Keywords: Political science, methodological basis, the concept, analysis, political life.